’’ The prevailing communication styles of principals from the point of view of workers in basic education schools in the city of Jableh’’ - ميهوب ميس (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The aim of the research is to identify the prevailing communication methods among principals from the point of view of workers (teachers, administrators) in basic education schools in the city of Jableh, as well as to identify the differences they have according to the variables of job title, educational qualification and years of experience. The sample was (322) teachers and administrators, (150) administrators and (172) teachers working in basic education schools. To achieve these goals, the researcher followed the descriptive research method, and used a measure of communication methods (prepared by the researcher), which consisted of (30) items. The study showed the following results: -The communication methods prevailing among managers are the horizontal communication style -There are no statistically significant differences in the communication methods of the research sample individuals according to the variables of job title, educational qualification and years of experience.